1‐Naphthol Synthesis through Base‐Promoted SNAr Reactions of ortho‐Haloacetophenones Followed by Lewis‐Acid‐Catalyzed Cyclization. Issue 5 (29th March 2016) - Yu, Xiaoqiang; Zhu, Peihong; Bao, Ming; Yamamoto, Yoshinori; Almansour, Abdulrahman I.; Arumugam, Natarajan; Kumar, Raju Suresh
Abstract: An efficient method was developed for the synthesis of 1‐naphthols through NaO t Bu‐promoted SN Ar reaction of ortho ‐haloacetophenones followed by Lewis acid CuI‐catalyzed intramolecular condensation and isomerization. 1‐Naphthol derivatives were obtained in satisfactory yields from aryl bromide and aryl iodide substrates. Abstract : Put a ring on it : 1‐Naphthol derivatives were synthesized through NaO t Bu‐promoted SN Ar reactions of ortho ‐haloacetophenones followed by CuI‐catalyzed intramolecular condensation and isomerization.